The substrate specificity switch FlhB assembles onto the export gate to regulate type three secretion - Lucas Kuhlen (Nature Portfolio, 2020)
Export of proteins by type three secretion systems occurs through an export gate that is localized in the periplasm. Here, the authors present the cryo-EM structure of the Vibrio mimicus export gate complex with FlhB, which plays a major role in switching of the specificity of secretion substrates and propose a mechanism for export gate opening.